Controle não linear de posição e vibração de manipuladores robóticos com juntas e elos flexíveis utilizando materiais inteligentes - Lima, Jeferson José de (2015)
This work presents the modeling and control of robotic manipulators with flexible characteristics, both joints as in the links. The mechanical model is obtained by Lagrangian formulation. Control strategy is considered as actuators DC motors (Direct Current) and actuators classified as smart materials such as shape memory alloy (SMA) and Magnetorheological brake (MR). The law of implemented control is based on optimal control techniques for dynamic systems, this control is given the name of SDRE control (State Dependent Ricatti Equation). To demonstrate the efficiency and control the stability of the numerical simulations are presented in three systems: the first demonstrates control of a robotic manipulator with two hard links, two flexible joints and adding torque control in the manipulator of the link through actuator MR. The second case concerns the control of a system with three links, one being flexible, rigid and two of two flexible joints, is used as actuators DC motors of the links and a coupled SMA actuator to the flexible beam. Aiming to validating the control position by DC motor and the influence of the flexible shaft in system dynamics a manipulator prototype with two rigid links and two flexible joints was made. Numerical and experimental results demonstrated the links positioning control efficiency through SDRE control and the influence of the flexible shaft in the dynamics of robotic manipulator.